Пример. [latex] \frac{11}{15} [/latex] - [latex] \frac{3}{10} [/latex] + [latex] \frac{1}{45} [/latex]

Пример. [latex] \frac{11}{15} [/latex] - [latex] \frac{3}{10} [/latex] + [latex] \frac{1}{45} [/latex]
Гость
Ответ(ы) на вопрос:
Гость
11/15(умножаем на 6)-3/10(умножаем на 9)+1/45(умножаем на 2)=66/90-27/90+2/90=41/90
Гость
[latex] \frac{11}{15} - \frac{3}{10} + \frac{1}{45} = \frac{11*6}{15*6} - \frac{3*9}{10*9} + \frac{1*2}{45*2}= \frac{66}{90} - \frac{27}{90} + \frac{2}{90} = \frac{66-27+2}{90} = \frac{41}{90} [/latex]
Не нашли ответ?
Ответить на вопрос
Похожие вопросы